Moderate to severe leukocytosis with vasopressor use is associated with increased mortality in trauma patients. (May 2022) - Hasjim, Bima J; Grigorian, Areg; Stopenski, Stephen; Swentek, Lourdes; Sun, Beatrice; Livingston, Joshua K; Williams, Barbara; Nastanski, Frank; Nahmias, Jeffry
Background: Leukocytosis is a rise in white blood cell (WBC) count and clinical outcomes of moderate to severe leukocytosis in trauma patients have not been described. We hypothesized that trauma patients with severe leukocytosis (SL; ≥40.0 × 10 9 leukocytes/L) have higher rates of in-hospital complications and mortality than those with moderate leukocytosis (ML; 25.0–39 × 10 9 leukocytes/L). Methods: We performed a retrospective analysis (2010-2017) on trauma patients developing ML or SL at a single Level-I trauma center. A multivariable logistic regression analysis for risk factors were performed. Results: From 15, 807 trauma admissions, 332 (2.1%) had ML or SL. Of these, 308 (92.8%) were ML and 24 (7.2%) were SL. Patients with ML and SL reached their peak WBC count in 1 and 10 days after admission respectively (p < 0.001). SL patients suffered higher rates of in-hospital complications (p < 0.05) and mortality compared to those without ML or SL (14.5% vs. 3.3%, p < 0.001). Between ML and SL, mortality rates rose with leukocytosis severity (13.3% vs. 29.2%, p = 0.03). Among all patients with ML or SL, vasopressor use was the strongest independent risk factor for mortality (OR 12.61, p < 0.001). Conclusion: Clinicians should be weary of the increased mortality rates and in-hospital complications in SL patients. Among patients with ML or SL, vasopressor use, rather than SL, was the strongest predictor of mortality. Patients with ML had a quicker time course to peak leukocytosis compared to SL, suggesting these two entities to be distinct in etiology and outcome, warranting future research.